Academic Visit of Students and Doctoral Candidates to Rome and the Vatican - Łuczak, Małgorzata Katarzyna (Prawo Kanoniczne, 2025)
The study concern an study visit undertaken by postgraduate students, students and graduates of the Faculty of Canon Law at Cardinal Stefan Wyszyński University in Warsaw and the Faculty of Canon Law and Administration at the John Paul II Catholic University of Lublin to Rome and the Vatican from 20 to 27 March 2025. The study vistit took place during the Jubilee of the Year 2025 under the theme „Pilgrims of Hope". The purpose of the trip was to deepen the participants' knowledge of the functioning of the various offices of the Roman Curia and its role in the governance of the Catholic Church, as well as to familiarize themselves with the cultural and spiritual heritage of Rome. The participants encountered with representatives of the Pontifical Commission for the Protection of Minors, the Supreme Tribunal of the Apostolic Signatura, the Pontifical Gregorian University, the Dicastery for the Doctrine of the Faith, the Embassy of the Republic of Poland to the Holy See, the Dicastery for Legislative Texts, the Dicastery for the Clergy, the Dicastery for Institutes of Consecrated Life and Societies of Apostolic Life, the Tribunal of the Roman Rota and the Pontifical University of the Holy Cross. The programme featured visits to the Vatican Museums, the Catacombs of St. Sebastian and the four Papal Basilicas in Rome. This study visit proved to be of exceptional educational value. It allowed students not only to consolidate the knowledge they already possessed, but also for its practical application and active participation in discussions. Moreover, it fostered the exchange of experience and strengthened cooperation between the academic centers of the Catholic University of Lublin and Cardinal Stefan Wyszynski University. The author emphasizes the importance of integrating theoretical knowledge with practical experience as a key aspect of the canon law curriculum.